MeCP2 Deficiency Disrupts Kainate-Induced Presynaptic Plasticity in the Mossy Fiber Projections in the Hippocampus - Bertoldi, Maria Laura; Zalosnik, Maria Ines; Fabio, Maria Carolina; Aja, Susan; Roth, German A.; Ronnett, Gabriele V.; Degano, Alicia L. (Frontiers in Cellular Neuroscience, 2019)
Methyl Cytosine Binding Protein 2 (MeCP2) is a structural chromosomal protein involved in the regulation of gene expression. Mutations in the gene encoding MeCP2 result in Rett Syndrome, (RTT) a pervasive neurodevelopmental disorder. RTT is one of few Autism Spectrum Disorders (ASDs) whose cause was identified as a single gene mutation. Remarkably, abnormal levels of MeCP2 have been associated to other neurodevelopmental disorders, as well as neuropsychiatric disorders. Therefore, many studies have been oriented to investigate the role of MeCP2 in the nervous system. In the present work, we explore cellular and molecular mechanisms affecting synaptic plasticity events in vivo in the hippocampus of MeCP2 mutant mice. While most studies addressed postsynaptic defects in the absence of MeCP2, we took advantage of an in vivo activity-paradigm (seizures), two models of MeCP2 deficiency, and neurobiological assays to reveal novel defects in presynaptic structural plasticity in the hippocampus in RTT rodent models. These approaches allowed us to determine that: MeCP2 mutations alter presynaptic components, i. e., disrupts the plastic response of mossy fibers to synaptic activityand results in reduced axonal growth which is correlated with imbalanced trophic and guidance support, associated with aberrant expression of BDNF and Sema3F. Our results also revealed that adult-born granule cells recapitulate maturational defects that have been only shown at early postnatal ages. As these cells do not mature timely, they may not integrate properly into the adult hippocampal circuitry. Finally, we performed a hippocampal-dependent test that revealed defective spatial memory in these mice. Altogether, our studies establish a model that allows us to evaluate the effect of the manipulation of specific pathways involved in axonal guidance, synaptogenesis, or maturation in specific circuits and correlate it with changes in behavior. Understanding the mechanisms underlying the neuronal compromise caused by mutations in MeCP2 will provide information on the pathogenic mechanism of autistic spectrum disorders and improve our understanding of brain development and molecular basis of behavior.